Human papilloma virus (HPV) and prostate cancer (PCa): The potential role of HPV gene expression and selected cellular MiRNAs in PCa development. (May 2022) - Khatami, Alireza; Nahand, Javid Sadri; Kiani, Seyed Jalal; Khoshmirsafa, Majid; Moghoofei, Mohsen; Khanaliha, Khadijeh; Tavakoli, Ahmad; Emtiazi, Nikoo; Bokharaei-Salim, Farah
Abstract: Background: Prostate cancer (PCa) is one of the most common and health-threatening cancers in men worldwide. The human papillomavirus (HPV) is considered one of the organisms with the potential to be involved in the progression of this cancer. In the present study, we evaluated the association between the expression levels of HPV genes with the expression of selected cellular miRNAs (miR-19a, miR-21, miR-23b, miR-34a, miR-150–5p, and miR-155) and their targets genes (P53, Rb, c-Myc, TIMP-1, MMP-2, MMP-9, PDCD4, Bcl-2, and Survivin) in PCa tissue samples. Methods: HPV detection and genotyping were performed on the tissues of 112 PCa patients and 39 healthy individuals. The expression profile of miRNA was evaluated by SYBR Green-based real-time PCR. As well Human Survivin ELISA Kit was utilized to determine the concentrations of Retinoblastoma, P53, survivin, Bcl-2, c-Myc, TIMP-1, MMP-2, MMP-9, and PDCD4 in the prostate tissues. Results: According to our findings, HPV genome was detected in 28.7% (21/73) of PCa tissue specimens and 17.94% (7/39) control samples. There was no significant association between the presence of HPV infection with PCa (OR = 2.01, 95%CI = 0.8–5.68, P = 0.102). We found that mean expression level of miR-19a (3.7 ± 4.3, p-value: 0.0007), and −21 (2.5 ± 2.8, p-value<0.0001) were significantly higher and miR-23b (−2.14 ± 3.08, p-value: 0.003) and −34a (−3.12 ± 3.28, p-value: 0.0001) levels were significantly lower in PCa tissue samples than in control tissue samples. Conclusion: Present research indicated that HPV positive PCa has a distinct miRNA profile compared with HPV negative PCa. Highlights: The human papillomavirus (HPV) is considered the organism with the potential to be involved in the progression of PCa. HPV genome was detected in 28.7% (21/73) of PCa tissue specimens and 17.94% (7/39) control samples. There was no significant association between the presence of HPV infection with PCa (OR = 2.01, 95%CI = 0.8–5.68, P = 0.102). We found that expression level of miR-19a (3.7 ± 4.3, p-value: 0.0007), −21 (2.5 ± 2.8, p-value<0.0001) were significantly higher and miR-23b (−2.14 ± 3.08, p-value: 0.003) and −34a (−3.12 ± 3.28, p-value: 0.0001) levels were significantly lower in PCa tissue samples than in controls. The expression patterns of studied proteins are significantly different between the HPV-positive PCa group and HPV-negative PCa group. As well, miR-155, and miR-34a can probably act as novel biomarkers for distinguishing HPV-positive samples from HPV-negative samples.